EFFECT OF EX-DIVIDEND DATE ON STOCK RETURNS OF NIFTY STOCKS IN INDIA - Rawat, Lakshmi; Jessica, Mary (PEOPLE: International Journal of Social Sciences, 2016)
In the present study we examine the impact of ex-dividend day on stock returns to Indian companies listed under Nifty 50 companies during the period 2011-2015 both inclusive. We examine the daily abnormal returns for 61 days, 31 days and 11 days event window using event study methodology with an estimation period of 250 days prior to ex-dividend date. Abnormal returns have been calculated using Market Model with Nifty index as proxy for market returns. To test the significant of Average Abnormal Returns both parametric and non-parametric tests has been used, that is paired t –test and Wilcoxon Signed Rank Test. We conclude from the analysis of the study that AAR have been statistically significant for 31 days event window, with an average mean of 0.0944 during preannouncement and -.0960 average mean during post announcement. This implies that, there had been very high actual returns during the pre-announcement period indicating positive market reaction.